Guía de citados y referencias según la séptima edición del estilo APA - Espinoza Coila, Michael (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2022)
The Faculty of Legal and Political Sciences of the National University of the Altiplano of Puno, has made an effort to provide teachers and students with a text on the APA in Spanish, which concerns the structures of the cited, references, figures and tables.